Sudut Pandang Kemiskinan di Perkotaan Dan Perdesaan Terhadap Lingkungan - Nurwahyuni, Intan; Firiyani, Salmah; Dermawan, Deris (Universitas Labuhanbatu, 2022)
The environment is an important part of sustainable development because it takes into account all funding as well as human welfare policies, programs, activities, and decisions. The government continues to focus primarily on poverty, despite the fact that it is a multifaceted problem. Instead, the prolonged Development Goals (SDGs) include 2 agendas: reducing poverty and changing the environment. Due to limited information, this study used regression panel data in the province of Indonesia, to investigate the relationship between urban and rural poverty and the quality of the area from 2016 to 2020. Urban poverty and income inequality significantly degrade the quality of the area. according to research, poor people living in urban areas are more likely than poor people living in rural areas to damage the environment. Similarly, environmental quality suffers from large levels of income inequality. The resulting disparity in the quality of the area can be related to the presumption of a large standard of living between the poor in urban and rural areas.